Determination of Echimidine and Heliotrine in Tropical Honey by LC-MS/MS / Nurfayyadhah Omar - Omar, Nurfayyadhah (2014)
Objective: The aim of this study was to determine the presence of echimidine and heliotrine in tropical honey available in Peninsular Malaysia. Methodology: Thirty samples of tropical honey consists of pure honey and retail honey were randomly purchased from local supermarket all over Malaysia. The determination of pyrrolizidine alkaloids (PAs) are then analyses using LC-ESI-MS/MS with some modification. The linearity, recoveries, LOO and LOQ were determined in this study. Results: 13.33% and 6.66% of the honey samples were contaminated with echimidine and heliotrine, concentration varying from 8. 773 to 22.033 ng/g and 13.100 to 19.892 ng/g, respectively. The linearity were achieved with R2 0.99, it shows good recoveries and the LOO was 1 ng/g as well as LOQ was 4 ng/g. Conclusion: The results showed that 20% of total analysed tropical honey samples were contaminated with PAs.